The Implementation of Human Resource Management in Improving Teacher Professionalism at MadrasaJunior High School (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to analyze human resource recruitment at Madrasa Junior High School Al-Faaizun Watang Palakka Bone Regency, the selection of human resources at Madrasa Junior High School Al-Faaizun Watang Palakka Bone Regency, human resource development program at Madrasa Junior High School Al-Faaizun Watang Palakka Bone Regency. This research is qualitative research with the research location at Madrasah Tsanawiyah Al-Faaizun Watang Palakka Bone Regency. Data was collected through interviews, observation, and documentation. Then, data processing and analysis techniques are carried out through three stages, namely data reduction, presentation, and drawing conclusions. The results of the research show that human resource recruitment was carried out at Madrasa Junior High School Al-Faaizun Watang Palakka, Bone Regency, namely, firstly, preparation for the recruitment of educators, secondly, the distribution of announcements regarding the acceptance of educators was carried out in a closed manner, and thirdly, accepting teacher applications. Human resource selection was carried out at Madrasa Junior High School Al-Faaizun Watang Palakka, Bone Regency, namely administrative selection to determine the completeness of applicant files according to predetermined qualifications and interview selection to obtain in-depth information about applicants. The human resource development program at Madrasa Junior High School Al-Faaizun Watang Palakka is carried out through teacher qualification improvement programs, supervision programs, subject teacher deliberation empowerment programs (MGMP), and participating in scientific meetings such as workshops, seminars, good training held at madrasas and outside the madrasah. This research implies that the distribution of announcements on teacher recruitment should be done openly through brochures, advertisements, and other social media so that it is easier for the public to get information on teacher recruitment from these institutions, with needs.